Pengaruh Lingkungan Fisik terhadap Kepuasan Mahasiswa di Universitas Djuanda Bogor - Alisya Subhani; Firda Fauziah; Naila Nurmilah; Jefri Maulana; Nawa Julika; Haekal Muhamad (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate the influence of the physic|al environment on student s|atisf|action |at Dju|and|a University, Bogor. |A qu|antit|ative method with |a survey |appro|ach w|as used to collect d|at|a from 50 students through questionn|aires. Multiple line|ar regression |an|alysis using SPSS version 26 reve|aled th|at the qu|ality of the physic|al environment—which includes |aspects such |as |air qu|ality, lighting, color, |and sound—h|as |a positive |and signific|ant imp|act on student s|atisf|action. These findings suggest that improving the physical environment can be an effective strategy to enhance student satisfaction and academic achievement